Finding geolocation of map image - Chawasit Tengtrairatana (2018)
© 2017 Copyright is held by the owner/author(s). This paper presents a novel framework to find a geolocation from a given map image. The proposed system extracts a road network and place names from the map image. The place names are used as the references and are queried on existing online map services to obtain their locations. The system retrieves the road network around that area then nodes from two sources of the road network are matched. For map registration, set of features based on relative positions, junction shapes and topological relations are proposed. The proposed framework can provide satisfying results in preliminary experiments.